Incidence of Adenocarcinoma with Gleason Grade in Clinically Enlarged Prostate Glands - Abeer; Kalsoom, Farah; Malik, Anum; Khwaja, Aneela; Alvi, Nusrat; Ejaz, Asma (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Prostatic cancer is the 2nd most common malignancy in men. The understanding of incidence of malignancy along with Gleason grading of tumor is significant that led the development of investigations for early detection and prompt treatment of patients Aims: The aim of this study is to determine the incidence of malignancies with Gleason grade in patients with clinically enlarge prostate glands. Materials and Methods: This is a descriptive cross sectional study conducted in Rahbar medical and dental college from 100 patients with clinically enlarge prostate glands from January 2018 to December 2020. Results: A total 100 prostatic biopsies were examined histologically from January 2018 to December 2020. Out of 100 biopsies 12(12%) cases were diagnosed as adenocarcinoma and 88 (88%) were benign lesions. The age of patients ranges from 52 to 95 years with mean age of patients was 73.5 years. Majority (41.66 %) of adenocarcinomas reported as Gleason grade group 5. In 16.66 % cases the malignancy was incidental as clinically there was no any suspicion of carcinoma. Perineural invasion was noted in 66.66% of adenocarcinomas, and in 16.66% of cases lymphovascular invasion was reported, that correlates with higher grade of tumor. Conclusion: Majority of the tumor diagnosed were in grade group 4 that shows increased death rate. Prostate cancer is continue to rise and screening of every patient with enlarge prostate should be done for early detection of malignancy.